Research in finance. Vol. 29 - Kensinger, John W. (Research in finance,, 2013)
The theme of Research in Finance vol. 29 is "Dealing with Crisis and Regulation." The volume begins with a examination of the European financial crisis, and possible solutions. Next is a look (using advanced empirical methods) at audit qualifications for accounting firms in Spain. Then the international aspect of the volume shifts to business strategies for competition between two major companies that dominate their industry in Mexico. The empirical analysis then shifts to a long-range (up to 50 years) look at anomalies in the real return on corporate equity compared with the realized returns from the real assets of corporations. This look at the value of real assets compared with financial assets is complemented by a look at the stabilizing influence of the recently expanding commodity futures trading in oil and gold. Then our attention shifts to regulation and some unintended consequences. Over the past ten years in the United States we have seen a substantial increase in going private transactions, accompanied by a substantial decline in initial public offerings. The next chapter considers whether this is simply a response to the regulatory burdens imposed by the Sarbanes-Oxley Act of 2002, or a response to other more deeply underlying factors in the financial markets. Then the regulatory examination shifts to the electric power grid, and some unintended consequences of the new regulations requiring retail utilities to buy all the power produced by wind and solar generators linked to their grid.The essence of the problem is that wind generators do not produce power at a consistent level, so conventional generators must be available to pick up the slack when the wind is not blowing strongly. The conventional generating plants must be ready to spool up quickly when needed. Then the conventional generating plants must be ready to spool down quickly when the wind generators begin producing strongly. Frequent spooling up and down places significant stress upon the conventional generators, increasing maintenance costs while at the same time reducing revenues.